From standardised to targeted survey procedures for tackling non-response and attrition - Peter Lynn (Survey Research Methods, 2017)
Recent decades have seen a gradual shift away from surveys in which all procedures are completely standardised towards a variety of approaches (tailored, responsive, adaptive) in which different sample members are treated differently. A particular variant of the non-standardised approach involves applying to each of a number of subgroups of the sample a targeted design feature (or set of features) that is identified in advance of field work and is not then modified during field work. Thus, the design is not “responsive.” As procedures are applied to broad subgroups, they are not “tailored” either. Targeted designs may be seen as a sub-category of adaptive designs. The effectiveness of targeted designs depends partly on the richness of information available about sample members prior to field work. For this reason they have mainly been implemented on panel surveys and mainly to address non-response and attrition. This article reviews the development of targeted designs in recent years, discusses the objectives of such designs, provides a framework for consideration of these designs, and outlines ways in which targeted designs might usefully develop in the years ahead.